Filosofi som/og/om populærkultur - Irwin, William (Slagmark - Tidsskrift for idéhistorie, 2018)
In this article the author explains the motivation for the philosophy and popular culture genre of books. He also defends the genre against its critics. Ultimately the author makes the case that the philosophy and popular culture genre of books are committed to disseminating philosophy in a Socratic spirit and manner. Oversat fra engelsk af Jakob Rønn Bohnsen